Dynamics of an oncolytic virus model. (February 2021) - Zhang, Jun
Abstract: An ODE model for oncolytic virus dynamics with four parameters is discussed. Although it is hard to obtain the explicit expressions of coordinates of equilibria, we find distribution of equilibria qualitatively, and obtain the exact number of equilibria and their qualitative properties. We further give a complete analysis on local bifurcations such as saddle–node, Bogdanov–Takens, and Hopf bifurcations. Resultant elimination is applied to decompose the semi-algebraic varieties of Lyapunov quantities under the restriction of biological meaning, and we show that the weak focus is of order at most 3.